Effects of hydrophilic polymer-coated polysulfone membrane dialyzers on intradialytic hypotension in diabetic hemodialysis patients (ATHRITE BP Study): a pilot study - Kenji Tsuchida (Renal Replacement Therapy, 2017)
Abstract Background Intradialytic hypotension (IDH) is a common clinical manifestation associated with poor prognosis in hemodialysis (HD) patients. HD patients who suffer from diabetic nephropathy (DN) are increasing and diabetes is a major cause of IDH. Effective interventional treatments for IDH have yet to be fully evaluated. The aim of this multicenter prospective study is to clarify the effect of biocompatible hydrophilic polymer-coated polysulfone (PS) membrane, TORAYLIGHT® NV (NV) dialyzers on IDH. Methods This is a prospective stratified-randomized multicenter trial. Forty DN patients undergoing HD and receiving two or more times of treatments for IDH per month were enrolled in this study. They were stratified by the number of treatments for IDH and divided to two groups using NV or conventional PS/polyethersulfone (PES) dialyzers. The number of treatments for IDH and changes in systolic blood pressure (SBP) were monitored for 6 months. Patients’ demographic and clinical characteristics were also collected at enrollment and the last month of the observation period. In order to clarify the patient characteristics that induced preferable effects by using NV dialyzers, responders were defined as the patients whose average SBP falls in 1 month improved from over 30 mmHg to no more than 30 mmHg. Results The total number of treatments for IDH decreased significantly in NV group, even though pre-dialysis body weight and ultrafiltration volume were similar. In addition, patients using NV had significantly higher post-dialysis SBP and the lowest SBP during HD at sixth month compared as those in PS/PES group. NV responders had valuables suggesting malnutrition and microinflammation, and better lipid profiles than non-responders. However, the representative markers related to nutritional status, arteriosclerosis, and inflammation were not improved by NV treatment. Conclusions NV had preferable effects on IDH in DN HD patients. Our results suggest the usefulness of NV as a possible method to deal with IDH. Further studies are needed to clarify the mechanism of NV effects on hemodynamic status. Trial registration This study was registered on September 26, 2013, in the University Hospital Medical Information Network-Clinical Trials Registry in Japan (Study ID: UMIN000011872 ).